Externalization Of Systematic Values of Wahyu Hidayatullah - In Constructing Miniature Islamic Civilization - Yahya, Irfan; Kasnawi, M Tahir; Abdullah, Suparman; Hasbi, Hasbi (Journal of Asian Multicultural Research for Social Sciences Study, 2021)
The values of the Systematic of Revelation as the basic -/pattern according to what the Hidayatullah - understands, believes, and practices in carrying out the process of social creation of a miniature Islamic Civilization are the topic of this study. The purpose of this research is to examine the process of externalizing Systematic Wahyu ideals like the Hidayatullah -’ - in carrying out social construction activities in a tiny Islamic civilisation. This research looks at the reality of the Hidayatullah - congregation’s consciousness, which reveals things about reality and the interpretation of the Systematic of Revelation as a -/archetype that is employed as a social construction reference. The process of externalizing the values of Systematic Revelation is a conscious, structured, and systematic effort by Hidayatullah actors to create humans as abdullah (servants of Allah) and caliph (representatives) of Allah SWT on earth, based on revelation’s guidance, in order to build Islamic civilization. The Islamic boarding School Campus is employed as a model of Islamic civilisation, with all cadres, members of the congregation, and their students demonstrating faith in all parts of everyday life. Internalized Hidayatullah players objected to the values that are consistently presented and then generate cadres capable of providing enormous advantages to society. This corresponds to Berger’s notion that human selfhood cannot possibly remain silent within itself, in a closed sphere, before moving outside to express itself in the world around it. Externalization is essentially what human selfhood is accomplishing.